Fusobacterium nucleatum induces colon anastomosis leak by activating epithelial cells to express MMP9 - Shi, Shang; Liu, Yang; Wang, Zhiyue; Jin, Xiangren; Yan, Wei; Guo, Xiao; Lin, Baiqiang; Wang, Haoran; Li, Bowen; Zheng, Jianjun; Wei, Yunwei (Frontiers in Microbiology, 2022)
Background Despite advances in anastomotic techniques and perioperative care, the incidence of anastomotic leak (AL) has not substantially decreased over time. Although it is known that AL etiology is multifactorial and the mechanisms involved remain unclear, there is accumulating evidence pointing at AL related to gut microbiota. Method We firstly performed a clinical study to analyze the gut microbiota between colorectal cancer patients who developed AL and those who did not (nAL) using 16S-rRNA sequencing and quantitative real-time PCR to identify AL risk bacterial taxa. Then we built a rat anastomosis model and performed a bacteria transplantation to ensure the cause-effect relationship. The anastomotic healing score was used to evaluate the healing of anastomosis. In addition, we assessed the adhesion ability of bacteria by staining with fluorescein isothiocyanate and attachment assay. The expression of matrix metalloproteinase 9 (MMP9) was detected by western blot, and the activity was detected by gelatin zymography. Results We found that the abundance and positive rate of Fusobacterium nucleatum (Fn) were higher in the AL patients. Exposure of the rat’s colon anastomosis to Fn contributes to the loss of submucosa collagen I and III, leading to AL’s pathogenesis. Fn can attach to the gut epithelial cells and stimulate intestinal MMP9 expression in vitro and in vivo. We further confirmed that these effects of Fn depended on the E-cadherin/β-catenin signaling pathway. Conclusion This work demonstrates that Fn attaches and then stimulates the expression of epithelial cells MMP9 by the E-cadherin/β-catenin signaling pathway. These effects contribute to collagen break down in the intestinal tissue, finally leading to AL.